PENGEMBANGAN MEDIA PEMBELAJARAN IKRAR BERBASIS VIDEO UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA KELAS VII - Jakaria, dimas (Pendidikan Islam Pascasarjana IAIN Jember, 2019)
This study aimed to obtain video based IKRAR learning media development which are valid, practical, and effective. The subjects of this research were the eigth grade students of MTs Al Hidayah. In this study, the developed teaching learning devices consisted of learning media and teacher’s guide book. The learning media is a series of video which presenting the mathematical lesson. The learning media was constructed according to IKRAR learning model. Teacher’s guide book content is the instruction of how to use the learning media in lesson. Validity, practicality, and effectiveness of the teaching learning devices were validated based on the expert judgement validation, teachers and students response, as well as the results of the research on the developed teaching learning devices. The development of the teaching learning devices followed a research design’s procedures from Plomp includes the following phasespreliminary research, prototyping, and assessment. The results showed that the learning media had been fulfiling the expected criteria of validity, practicality, and effectiveness. The results of the study using this learning media showed an improvement of students’ mathematics learning achievement.